The impact of implicit theories on resilience among Chinese nurses: The chain mediating effect of grit and meaning in life - Tang, Yixun; He, Changjiu; Feng, Lanling; Wu, Dongmei; Zhou, Xiaojun; Li, Tao; He, Lina; Cai, Qiao; Yue, Yuchuan (Frontiers in Psychology, 2022)
Implicit theories refer to two assumptions that people make about the malleability of one’s ability, also known as mindsets. People have two different implicit theories, entity theory, and incremental theory. They constrain and regulate people's understanding and responses to an individual's behavior, leading to different social cognitive patterns and behavioral responses. Resilience refers to a person’s ability to recover from a traumatic event and has long been recognized as a protective factor for mental health. Although previous studies showed that individuals' implicit theories are associated with resilience, this relationship has received little attention in the nursing population, it is unclear which variables may contribute to explaining the relationship between implicit theories and resilience. Therefore, the current study aims to deeply explore the relationship between implicit theories and the resilience of Chinese nurses. In addition, we also seek to demonstrate the chain mediating effects of grit and meaning in life on this relationship. We surveyed 709 Chinese nurses through online questionnaires using the self-made demographic questionnaire, the Implicit Theories Scale (ITS), the Short Grit Scale (Grit-S), the Meaning in Life Questionnaire (MLQ), and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). After controlling for demographic variables such as age, gender, educational background, marital status, professional title, and working years, the results reveal positive associations between Chinese nurses' implicit theories and their resilience, and grit and meaning in life play a partial mediating role in this relationship, respectively. Furthermore, grit and meaning in life play a chain mediating role between implicit theories and resilience. These findings contribute to understanding the psychological impact mechanism of implicit theories on nurses' resilience and provide a theoretical basis for nursing managers to formulate strategies to improve nurses' psychological resilience.